(untitled) (Web of Teachers: Inderscience Research, 2024)
Currently, there are innovative approaches to the development of physical qualities. Using the example of the youth workout movement, it became possible to build up the training process with the complex impact on the development of physical qualities. The article presents the developed methodology of the extracurricular activities with the use of workout means among old boys for the development of physical qualities, individualized according to age characteristics.